The Main Character of the Book of Esther: The Contribution of the Textual Divisions and the Assigned Titles of the Book of Esther to Uncovering Its Protagonist - Goswell, Gregory (Journal for the study of the Old Testament, 2021)
Scrutiny of the traditional textual divisions of the Hebrew version of the book of Esther—the sedarim, the Hebrew paragraphs and the Latin chapters – throws light on whom some ancient readers thought was the main character (protagonist) of the book. The sedarim appear to favour Mordecai’s role over Esther’s in the events narrated, whereas the positioning of the Hebrew paragraph breaks apportions attention more evenly between Esther and Mordecai, who each sought the welfare of the Jewish people. The chapter divisions show an interest in all three leading characters namely, Esther, Mordecai and Ahasuerus. In terms of assigned titles, the book was given the alternate names of Esther and Ahasuerus. It is plain, therefore, that early readers did not come to a settled conclusion as to who is the main character; however, it is clear that the role of Ahasuerus cannot be ignored and that the Persian king must be a candidate for the main character of the book.